Green reinforcement techniques: Using natural hemp and cotton ropes to enhance the structural integrity of short-span RC beams - Thansirichaisree, Phromphat; Ejaz, Ali; Saingam, Panumas; Mohamad, Hisham; Hussain, Qudeer; Chaimahawan, Preeda; Bhadrakom, Bhakapong; Buddhawanna, Saharat (My University, 2025)
This study evaluates the structural performance of natural fiber ropes—hemp and cotton—as sustainable strengthening materials for short-span reinforced concrete (RC) beams. A total of 15 beams were tested under four-point bending: one unstrengthened control beam and 14 strengthened beams divided into three groups. Group I included three cotton-strengthened beams using two strip configurations (Type A: 50 mm wide, Type B: 100 mm wide) and one full wrap (Type C). Group II comprised nine hemp-strengthened beams reinforced with 1, 2, or 3 layers in various configurations, while Group III included two CFRP-strengthened beams using a single layer of CFRP strips (Types A and B). Beams strengthened with a single cotton or hemp rope layer exhibited inadequate shear resistance, showing concrete crushing or diagonal cracking. In contrast, two-layer hemp confinement led to more vertical cracking, indicating improved ductility. Results showed that cotton- and hemp-strengthened beams improved peak load capacity by 17 %–40 % and 22 %–78 %, respectively, compared to the control beam, while CFRP offered 36 %–51 % gains. Deflection capacity, indicating ductility, increased by 58 %–95 % for cotton, 42 %–155 % for hemp, and 71 %–145 % for CFRP. Full wrap configurations consistently provided the highest enhancements in both load and ductility, while among strip configurations, Type B outperformed Type A. Hemp ropes delivered higher load capacity due to their superior tensile strength, whereas cotton ropes exhibited greater ductility because of their higher fracture strain (13.5 % vs. 3.5 %). Energy dissipation improved with increased rope quantity and tighter strip spacing. The study also found that conventional FRP-based shear prediction models significantly overestimated the contribution of hemp confinement due to its larger diameter (2.1 mm), underscoring the need for revised modeling approaches. These findings demonstrate the technical feasibility, cost-effectiveness, and environmental advantages of using natural fiber ropes as alternative strengthening materials in structural retrofitting.
Keywords: Beam; Cotton; Hemp; Natural confinement; Short span